APLICACIÓN DE FRAMES EN TEOREMAS MUESTRALES - Núñez Ramírez, Luis Miguel (2014)
A frame is the generalization of the concept of a basis in a vector space, in this context we study the technique of the frames, some of its properties, and itsapplications in sampling theory.